2016
DOI: 10.1093/heapro/daw020
|View full text |Cite
|
Sign up to set email alerts
|

Intersectoriality in Danish municipalities: corrupting the social determinants of health?

Abstract: Action on the social determinants of health (SDH) through intersectoral policymaking is often suggested to promote health and health equity. This paper argues that the process of intersectoral policymaking influences how the SDH are construed and acted upon in municipal policymaking. We discuss how the intersectoral policy process legitimates certain practices in the setting of Danish municipal health promotion and the potential impact this can have for long-term, sustainable healthy public policy. Based on et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
61
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(66 citation statements)
references
References 39 publications
4
61
0
1
Order By: Relevance
“…The value of collaboration has been stressed in guiding policy documents such as the Health in All Policy approach. While the goal in these approaches is for the different policy areas to collaborate towards better health, there is a risk of ending up framing health as a means to achieve the objectives of nonhealth sectors . A recent study shows that in some policy processes, health is framed as a means and as something distinct from other social issues to ensure legitimacy.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The value of collaboration has been stressed in guiding policy documents such as the Health in All Policy approach. While the goal in these approaches is for the different policy areas to collaborate towards better health, there is a risk of ending up framing health as a means to achieve the objectives of nonhealth sectors . A recent study shows that in some policy processes, health is framed as a means and as something distinct from other social issues to ensure legitimacy.…”
Section: Discussionsupporting
confidence: 85%
“…The authors claim that this approach actually narrows the scope of potential policies and interventions. Instead, the authors argue for targeting the causes of causes and the distribution of societal problems . The confusion surrounding the ownership of the drug prevention field is somewhat similar to the ongoing discussion of the framing of health in policy discussions.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 As Breton 3 notes, however, its efficacy is yet to be established and work published elsewhere suggests that it may in fact be counterproductive to its very aims. 8 Previously, colleagues and I have sought to bring conceptual clarity to this type of public health activity, which we view as a fundamentally different form of policy advocacy than public health has traditionally used. 9 We argued that HiAP is an example of an 'instrumental process-based intervention' (IPI).…”
mentioning
confidence: 99%
“…16 The interactions between the formal institutions that public health advocates for, and the informal institutional practices of actors, can be difficult to predict and can have serious unintended consequences. For example, Holt et al 8 found that using HiAP drew policy-makers away from the major drivers of ill-health such as housing and poverty, to focus on smallerscale behaviour-based interventions. This result is counter to the very goals of HiAP.…”
mentioning
confidence: 99%
“…through intersectoral working groups. Simultaneously, public health interventions contribute to a moral regulation of the population which maintains a narrow focus on individual lifestyle and health responsibility even if it is framed by a concern for the social determinants of health (Holt, Frohlich, Tjørnhøj-Thomsen, & Clavier, 2017). As Dew has it, 'public health appears as a prime candidate for fulfilling the role of religion in a society based on organic solidarity ' (2012, p. 144).…”
Section: The (Failed) Promise Of Intersectoral Working Groups and Othmentioning
confidence: 99%